PERSPEKTIF YURIDIS DAN ETIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 2/PUU-XX/2022 - Munawwar, Said (Legal Standing : Jurnal Ilmu Hukum, 2024)
The decision of the Constitutional Court Number 2/PUU-XX/2022 sparked an interesting theoretical debate. This decision provides space for former narcotics convicts to run in regional head elections. According to the Constitutional Court, the decision "whether or not" a person advances in political contestation, regardless of whether he is a former convict or not, only has the right to be determined by the people as the holder of the highest power in the state. This is a logical consequence of the adoption of democratic principles in Indonesia. Therefore, according to the Constitutional Court, any state institution has no right to limit a person's chances of winning in a political contest. The Court only added that the former narcotics convict was obliged to announce to the public that he was a former narcotics convict. As long as this is done, and it turns out that the people still accept themselves and their past, then the election is valid, and the former convict has sufficient legitimacy to lead a region. The Constitutional Court also considered that even if a person has been convicted, once he/she is released from detention, he/she still has the right to get a second chance to correct his/her mistakes. This paper attempts to examine from an ethical and legal perspective, on this decision. This paper will use a normative juridical research method, with a conceptual approach and a statutory approach. Based on the juridical and ethical analysis carried out, it proves that things are different from the court's legal considerations in the decision. From a juridical perspective, this decision fulfills the element of legal certainty. However, on the other hand, it is compete with the elements of justice and benefit.